KARAKTERISTIK KORBAN KECELAKAAN LALULINTAS DI KOTA MAKASSAR - Munawir Muhtar; Nur Ali; Muh. Isran Ramli (Jurnal Transportasi, 2008)
Abstract Traffic accident is a serious problem in the city of Makassar.  This study tries to describe the characteristics of traffic accident in that city. Samples were collected and surveys were conducted using interview and questionnaire techniques. The results show that the traffic accident victims in Makassar are dominated by students, with the age ranging from 16 years to 21 years. The largest portion of the victims in this city used motor cycles when involved in traffic accidents.Keywords: traffic accident, accident characteristic, and accident victim.